2015
DOI: 10.1068/b130171p
|View full text |Cite
|
Sign up to set email alerts
|

Spatial accessibility to amenities, natural areas and urban green spaces: using a multiscale, multifractal simulation model for managing urban sprawl

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…In this paper, we focus on the accessibility rules for shops, services, and leisure, as well as the population model. Fractalopolis also includes a "lacunarity" rule on a local scale (neighborhood), which was discussed by Yamu and Frankhauser [2].…”
Section: The Multifractal Planning Model Fractalopolismentioning
confidence: 99%
See 4 more Smart Citations
“…In this paper, we focus on the accessibility rules for shops, services, and leisure, as well as the population model. Fractalopolis also includes a "lacunarity" rule on a local scale (neighborhood), which was discussed by Yamu and Frankhauser [2].…”
Section: The Multifractal Planning Model Fractalopolismentioning
confidence: 99%
“…Previous studies have shown that, using fractal logic on a regional scale, either a Fournier dust or a Sierpiński carpet is very useful. On an urban scale, however, a Sierpiński carpet [2] or, when a higher densification is intended, monofractal logic is advantageous [34] for developing urban planning scenarios.…”
Section: From Theory To Applicationmentioning
confidence: 99%
See 3 more Smart Citations